Hooray for Hoppy! - Hopgood, Tim (Farrar Straus Giroux, 2014)
When Hoppy the rabbit wakes up on the first day of spring, he discovers a world full of wonderful things. He uses all five senses to sniff the fresh air, listen to the birds sing, taste the fresh grass, watch the lambs in the meadow, and touch the warm ground. Illustrated in bright, bold collage, this story about seasonal change and sensory perception makes a warm and cozy readaloud.